Pengaruh Desentralisasi Fiskal, Fiscal Stress, dan Kinerja Keuangan Daerah Terhadap Pertumbuhan Ekonomi di Kabupaten/Kota Provinsi Bali - Muryawan, Sang Made; Sukarsa, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.02.TAHUN 2016, 2016)
This study was conducted examine the effect of fiscal decentralization and fiscal stress economic growth in the province of Bali, either directly or through a local financial performance. The research data is secondary data taken from publications of Ministry of Finance, BPS and Bappeda each regency / city. The variables analyzed using path analysis to determine the direct and indirect influence of the variables  the research model . The results of this analysis revealed that fiscal decentralization variable indirectly and fiscal stress variables affects economic growth significantly through regional financial performance , fiscal decentralization variables and fiscal stress directly influence economic growth , and financial performance variables significantly influence economic growth. To promote economic growth in an era where the area of fiscal decentralization, local governments are expected to increase their fiscal capacity, through the development of commodity-based economic activity, the intensification and expansion of revenue and efficient financial performance.
Keywords: Desentralisasi fiskal, Fisca Stress, Kinerja keuangan, Pertumbuhan Ekonomi